A delicate balance between control and flexibility: Experiences of care and support among pre‐teenage children with type 1 diabetes and their families. Issue 2 (18th December 2020) - Pals, Regitze Anne Saurbrey; Coyne, Imelda; Skinner, Timothy; Grabowski, Dan
Abstract: For children with type 1 diabetes, the period of adolescence is associated with higher blood glucose levels and increased psychological distress compared to other age groups. Focusing on pre‐teens (9‐12 years) with type 1 diabetes and their families has been suggested as key to understanding and reducing these challenges. The aim of this study was to explore: 1, how diabetes affects family life, 2, experiences of and needs for support and 3, how care responsibilities are negotiated among pre‐teens with type 1 diabetes and their families. Data were obtained from four interactive workshops with pre‐teens (n = 17), their parents (n = 26) and their siblings (n = 14). Dialogue tools, for example quotes and picture cards, were used to facilitate discussion and reflection concerning family life with type 1 diabetes. Data analysis resulted in three themes: 1, diabetes takes up 'a lot of space', 2, giving and receiving support and 3, balancing control and flexibility. While diabetes took up significant space in the families, family members protected each other from their respective frustrations. The findings point to the significance of considering all key family members and their interactions in diabetes interventions. This includes balancing control and flexibility, negotiating responsibilities and building trust.